2002
DOI: 10.1021/jo0204754
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Biosynthesis of DTX-5a and DTX-5b by the Dinoflagellate Prorocentrum maculosum:  Regiospecificity of the Putative Baeyer−Villigerase and Insertion of a Single Amino Acid in a Polyketide Chain

Abstract: The biosynthetic origins of the diarrhetic shellfish poisoning toxins DTX-5a and DTX-5b have been elucidated by supplementing cultures of the producing organism Prorocentrum maculosum with stable isotope labeled precursors and determining the incorporation patterns by 13 C NMR spectroscopy. The amino acid residue in the sulfated side chain is found to originate from glycine, and oxygen insertion in the chain is shown to occur after polyketide formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 27 publications
(126 reference statements)
5
44
0
Order By: Relevance
“…5) (Macpherson et al, 2003). Incorporation patterns of the OA portion of these two analogs were revealed to be identical to DTX-4 (Needham et al, 1995;Wright et al, 1996).…”
Section: Dinophysis Toxinsmentioning
confidence: 88%
“…5) (Macpherson et al, 2003). Incorporation patterns of the OA portion of these two analogs were revealed to be identical to DTX-4 (Needham et al, 1995;Wright et al, 1996).…”
Section: Dinophysis Toxinsmentioning
confidence: 88%
“…Several precursor incorporation studies have also indicated that the PKS pathway participates in DSP toxin biosynthesis [137,138,139,140,141]. Glycolate from photorespiration is a deemed precursor of OA synthesis and side chains of DTX-5 (side chain c and d of R 5 in Figure 1).…”
Section: Putative Mechanism Of Dsp Toxin Productionmentioning
confidence: 99%
“…Glycolate from photorespiration is a deemed precursor of OA synthesis and side chains of DTX-5 (side chain c and d of R 5 in Figure 1). They are formed through the typical polyketide process, the consecutive addition of acetate and interruption by Favorskii-like rearrangement [138]. The side chains of DTX-5 ligate OA through an ester bond between glycolate-derived hydroxyl group and terminal carboxyl group of OA [140].…”
Section: Putative Mechanism Of Dsp Toxin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a large variety of methods have been used to synthesize this class of compounds [85]. The latest papers concerning the synthesis of 1,7-dioxaspiro [5.5]undecane subunits reported eventually improvements of the already reviewed spiroketalizations [86][87][88][89].…”
Section: Monospiranesmentioning
confidence: 99%